Kerja Sama Perpustakaan Intrakampus Institut Teknologi Bandung pada Layanan Multikampus melalui Fulfill Request - Sirojul Wahhaj, Ikhsan; Aisyah Putri, Ersha; Prijana, Prijana; Rachmawati, Tine Silvana (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2025)
Library services to meet the needs of users are a top priority for all libraries. The services provided have various forms, one of which is multicampus or interlibrary loan services. This research aims to find out and analyze how the multicampus service of the Bandung Institute of Technology Library meets the needs of users through fulfill requests by using the concept of implementing the Interlibrary Loan form of cooperation. This research uses a qualitative approach with an in-depth interview observation method. Interviews were conducted with 2 informants, each manager of the Bandung Institute of Technology Ganesha Campus Library and the Bandung Institute of Technology Jatinangor Campus Library. The result of this research is that the implementation of interlibrary loan in the multicampus service of the Bandung Institute of Technology Library is very useful for users and the library itself in boosting optimal service utilization. With fulfill request, the requested collection will be sent by ITB Central Library Ganesha Campus to ITB Library Jatinangor Campus. Information regarding collection requests that have been processed will be conveyed to the students concerned via email. That way, the needs of users can be met properly and maximally.